The Effects of Repeat-Dose Doxorubicin on Cardiovascular Functional Endpoints and Biomarkers in the Telemetry-Equipped Cynomolgus Monkey - Engwall, Michael J.; Everds, Nancy; Turk, James R.; Vargas, Hugo M. (Frontiers in Cardiovascular Medicine, 2021)
Purpose: Doxorubicin-related heart failure has been recognized as a serious complication of cancer chemotherapy. This paper describes a cardiovascular safety pharmacology study with chronic dosing of doxorubicin in a non-human primate model designed to characterize the onset and magnitude of left ventricular dysfunction (LVD) using invasive and non-invasive methods. Methods: Cynomolgus monkeys (N = 12) were given repeated intravenous injections of doxorubicin over 135 days (19 weeks) with dosing holidays when there was evidence of significantly decreased hematopoiesis; a separate group (N = 12) received vehicle. Arterial and left ventricular pressure telemetry and cardiac imaging by echocardiography allowed regular hemodynamic assessments and determination of LVD. Blood samples were collected for hematology, clinical chemistry, and assessment of cardiac troponin (cTnI) and N-terminal pro b-type natriuretic peptide (NT-proBNP). Myocardial histopathology was a terminal endpoint. Results: There was variable sensitivity to the onset of treatment effects, for example 25% of doxorubicin-treated animals exhibited LVD (e.g., decreases in ejection fraction) following 50–63 days (cumulative dose: 8–9 mg/kg) on study. All animals deteriorated into heart failure with additional dosing 135 days (total cumulative dose: 11–17 mg/kg). Reductions in arterial pressure and cardiac contractility, as well as QTc interval prolongation, was evident following doxorubicin-treatment. Both cTnI and NT-proBNP were inconsistently higher at the end of the study in animals with LVD. Measurements collected from control animals were consistent and stable over the same time frame. Minimal to mild, multifocal, vacuolar degeneration of cardiomyocytes was observed in 7 of 12 animals receiving doxorubicin and 0 of 12 animals receiving vehicle. Conclusions: This repeat-dose study of doxorubicin treatment in the cynomolgus monkey demonstrated a clinically relevant pattern of progressive heart failure. Importantly, the study revealed how both telemetry and non-invasive echocardiography measurements could track the gradual onset of LVD.